The Reorganization of Closely Held Firms and the “Opt Out” Problem - Douglas G. Baird (Washington University Law Quarterly, 1994)
This Article argues that the ability of parties to shape their investments in firms is responsible for the small costs of bankruptcy. The paper focuses on how investors can minimize the costs of bankruptcy even when they do not take steps to avoid it altogether.
Keywords: Closely held corporations; Corporate reorganizations; Close corporations; Bankruptcy reorganization